Les médias et les journalistes, interprètes de la société - Samuel Lamoureux (Communiquer)
This book review focuses on the book Les médias et les journalistes, interprètes de la société (2018). In this book, Nadège Broustau sheds light on the results of her doctoral thesis by the means of ulterior theoretical and methodological works. The author proposes a new way of analyzing the media discourse, here considered as a social archive: the study of the evolution of the media representations.